PENGUJIAN TEORI PECKING ORDER ATAS STRUKTUR MODAL (STUDI PADA ENTITAS TERBUKA DI INDONESIA) - Pontoh, Winston (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Insufficient working capital for investment activities is a condition which make shareholders and other firm insiders commonly consider to determine additional source of funds. The decision of shareholders and other firm insiders in determining the source of funds for investment activities shall determine the form of firm capital structure. This study uses 236 listed firms in Indonesia Stock Exchange as the sample and take their financial information in period of 2010 to 2015 as data. In term of hypothesis testing, this study conducts path analysis at significance rate of 5%. Result of analysis shows that capital structures for public firms in Indonesia are tend to apply the model of pecking order theory. Empirically, public firms in Indonesia tend to decrease their usage for long term debt in circumstance if they are facing certain business risk. The study also shows that, profitability is not the main factor in determining firm capital structure in Indonesia.Keywords : pecking order, capital structure, business risk, profitability, fixed assets